Graphene-Metal Hybrid Metasurface for Tunable Bandpass Filter in Terahertz Region - Ghosh S.K.; Das S.; Bhattacharyya S. (My University, 2025)
A graphene-metal hybrid metasurface with a tunable bandpass-filtering characteristics in the terahertz region has been introduced in this paper. The single unit of the design comprises of slotted metallic metasurface layers with square-shaped graphene metasurface rings on two opposite faces of silicon dioxide layers deposited on a foam substrate. The structural dimensions of the slots have been determined in such a way that the metastructure can provide a wide bandpass filtering response in between 3 THz and 10 THz with a 3-dB fractional transmission bandwidth of 29.64%. The bandpass response also become tunable in presence of the square-shaped graphene ring metasurfaces associated with the metal metasurfaces. By configuration, the design is thin (A/8.06) and its lattice size is A/5 obeying the effective homogeneity condition in the sub-wavelength domain. The transmission response is stable above 0.8 in magnitude scale upto 40° incident angles for both transverse magnetic and transverse electric polarizations of the EM wave. The transmission response of this spatial bandpass filter is also independent of the polarization of the incident EM wave. The proposed filter can be useful for THz communication system, THz imaging and spectroscopy systems, etc. © 2021 IEEE.